Deconstructing Gender Identity in Written on the Body by Jeannette Winterson - Hussein Dizayi, Saman Abdulqadir (International Journal of Psychosocial Rehabilitation, 2019)
Various authors write for different reasons. This can be to convey a message, entertain, teach, challenge their readers, and the status quo in the society in which they live. This paper focuses on how Jeanette Winterson's Written on the Body challenges the status quo on gender and identity. The article begins with an analysis of the ideas surrounding identity and gender in literature. After that, the paper looks at how the author dances around the gender of the narrator in the story to draw attention to it without confining them to a single gender or sexual identity. Finally, the paper makes the connection between Winterson's approach to the narrator and Jacques Derrida's deconstruction and its contributions to feminist theory. Derrida's deconstruction and feminist theory are both evident in Written on the Body as the basis for the deliberate fluidity of the narrator. The paper conducts qualitative analysis method in approaching an in depth looking at the objective of the paper